Role of individual and contextual effects in injury mortality: new evidence from small area analysis. (1st December 2002) - Borrell, C; Rodríguez, M; Ferrando, J; Brugal, M T; Pasarín, M I; Martínez, V; Plaséncia, A
Abstract : Objective: To analyse the role of individual and contextual variables in injury mortality inequalities from a small area analysis perspective, looking at the data for the city of Barcelona (Spain) for 1992–98. Setting: Barcelona (Spain). Methods: All injury deaths in residents older than 19, which occurred in the period 1992–98 were included (n=4393). Age and sex specific mortality rates were calculated for each educational level and each cause of death (traffic injuries, falls, drug overdose, suicide, other injuries). The contextual variables included were the proportion of men unemployed, and the proportion of men in jail, in each neighbourhood. Multilevel Poisson regression models were fitted using data grouped by age, educational level, and neighbourhood for each sex. Results: Death rates were higher in males, at the extremes of the age distribution (under 44 and over 74 years), and for lower educational levels. The results of the Poisson multilevel models indicate that inequalities by educational level follow a gradient, with higher risks for the population with no schooling, after having adjusted for the contextual variables of the neighbourhood. Such inequalities were more important in the youngest age group (20–34 years), as relative risk of 5.41 (95% confidence interval (CI) 3.9 to 7.4) for all injury causes in males and 4.38 (95% CI 2.3 to 8.4) in females. The highest relative risks were found for drug overdose. There was a contextual neighbourhood effect (the higher the deprivation, the higher the mortality) after having taken into account individual variables. Conclusion: The findings underscore the need to implement injury prevention strategies not only at the individual level taking into account socioeconomic position, but also at the neighbourhood level.